The effects of geographic and network ties on exploitative and exploratory product innovation. (5th May 2014) - Ozer, Muammer; Zhang, Wen
<x xml:space="preserve">Abstract</x> Addressing the inconsistent findings in the literature, we first distinguish the type of innovation and study the relationship of industrial clusters with exploitative and exploratory product innovation. Furthermore, we study how focal cluster firms' network ties with their suppliers and buyers in their clusters might moderate these relationships. Our empirical study showed that, while cluster membership enhanced firms' exploitative product innovation, it hindered their exploratory product innovation. Moreover, the results showed that focal cluster firms' network ties with their suppliers and buyers in their clusters strengthened the effects of cluster membership on exploitative product innovation. They also showed that focal cluster firms' network ties with their buyers but not suppliers in their clusters reduced the negative effects of cluster membership on exploratory product innovation. Copyright © 2014 John Wiley & Sons, Ltd.